Effects of metformin on fertilisation of bovine oocytes and early embryo development: possible involvement of AMPK3-mediated TSC2 activation. Issue 1 (February 2015) - Pikiou, Olympia; Vasilaki, Anna; Leondaritis, George; Vamvakopoulos, Nikos; Messinis, Ioannis E.
Summary Studies on bovine oocytes have revealed that the activation of adenosine monophosphate activated protein kinase (AMPK) by millimolar concentrations of metformin controls nuclear maturation. Tuberous sclerosis complex 2 (TSC2) has been identified as a downstream target of AMPK. The objective of this study was to investigate the effects of addition of low concentrations of metformin (1 nM to 10 μM) on the percentage of cultured cumulus–oocyte complexes (COC) giving rise to cleavage-stage embryos and AMPK-mediated TSC2 activation. Metformin was supplemented either throughout in vitro embryo production (IVP) or only during in vitro fertilization (IVF). COC were matured in vitro, inseminated, and presumptive zygotes cultured for a further 72 h post insemination before the percentage of COC that gave rise to zygotes and early embryo development was assessed. The presence of TSC2 in bovine embryos and its possible AMPK-induced activation were assessed by immunocytochemistry. Metformin had a dose-dependent effect on the numbers of cultured COC that gave rise to embryos. Drug treatment either throughout IVP or only during IVF decreased the percentage of ≥8-cell embryos (1 μM, P < 0.05; 10 μM, P < 0.01; and 0.1 μM, 10 μM, P < 0.01, respectively) and increased the percentage of 2-cell embryos (10 μM, P < 0.01 and P < 0.05 respectively). The percentage of cultured COC that gave rise to zygotes was not affected by metformin. TSC2 is expressed in early embryos. Metformin (10 μM) either throughout IVP or during IVF only, increased AMPK-induced PhosphoS1387-TSC2 immunoreactivity (P < 0.01) and this increase corresponded to the total TSC2 protein levels expressed in cells. Our results suggest that there is a dose-dependent negative effect of metformin on the ability of oocytes to cleave following insemination, possibly mediated through an AMPK-induced activation of TSC2.